2022
DOI: 10.2147/copd.s361929
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen, a Promising Marker to Evaluate Severity and Prognosis of Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Retrospective Observational Study

Abstract: Background Fibrinogen is increasingly being studied as an inflammatory biomarker in chronic obstructive pulmonary disease (COPD), but there are limited data on the role of fibrinogen in assessing the severity of acute exacerbation of COPD (AECOPD). This study aimed to explore whether circulating fibrinogen could be used as a surrogate to measure the severity and predict the prognosis of AECOPD. Methods A total of 535 AECOPD patients diagnosed at our center from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Elevated fibrinogen levels are linked to inflammation, exacerbations, severity, and mortality in chronic obstructive pulmonary disease [ 43 ].…”
Section: Fibrin(ogen) (Fn)mentioning
confidence: 99%
“…Elevated fibrinogen levels are linked to inflammation, exacerbations, severity, and mortality in chronic obstructive pulmonary disease [ 43 ].…”
Section: Fibrin(ogen) (Fn)mentioning
confidence: 99%
“…In patients with COPD, the occurrence of airflow limitation, thromboembolism, emphysema, and atherosclerosis are more prevalent when FIB levels exceed 4g/L. 128 , 129 Several studies have demonstrated a negative correlation between FIB level and FEV1, as well as a positive correlation with AE rate, readmission rate, exercise tolerance, and COPD mortality. This suggests that FIB level can serve as a biomarker for predicting the failure of NIV in COPD patients.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In addition, fibrinogen (FIB) is another promising serum biomarker for AECOPD as suggested in a previous study. 12 FIB is a glycoprotein synthesized by hepatocytes and its biological functions are closely related to blood coagulation, cell adhesion, proliferation and extension, phagocytosis and other activities. 13 Its molecular weight is the largest among all coagulogens, and it has a chain-like asymmetric structure, which can increase plasma thickening, contribute to the formation of tiny arterial thrombi in the lungs, and aggravate the injury to the lung.…”
Section: Introductionmentioning
confidence: 99%